University Students' Intentions Toward Entrepreneurial Careers in The Hospitality and Tourism Sector: Empirical Insights From The Techno-Savvy Generation in Higher Education - Asmar Yulastri; Ganefri Ganefri; Feri Ferdian; Elfizon Elfizon; Yudha Aditya Fiandra; Geovanne Farell (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2025)
This study investigates the impact of family support, entrepreneurial passion, entrepreneurial motivation, and techno-savvy culture on the entrepreneurial career intentions of university students in the hospitality and tourism sector, with entrepreneurship education as a moderating variable. Data were collected from 277 students at Universitas Negeri Padang’s Faculty of Tourism and Hospitality who had completed entrepreneurial courses. Partial least squares structural equation modeling was employed to analyze the data. The findings reveal that family support, entrepreneurial passion, and entrepreneurial motivation significantly influence students’ entrepreneurial career intentions, while techno-savvy culture showed no direct impact. However, entrepreneurship education significantly moderated the relationships between these factors and entrepreneurial intentions. These findings provide actionable insights for enhancing entrepreneurship education to foster innovation and career readiness in the hospitality and tourism industry. The study contributes to existing knowledge by elucidating the interplay of support systems, intrinsic motivations, and education in shaping entrepreneurial aspirations, offering a foundation for educational and policy reforms to boost entrepreneurship in the sector.